Values of Nubuwwah Narrative in the Qur’an: Examining the Value of Prophetic Education in the Qur’an Surah al- Saffat: 99-111 - Ashiddieqy, Mahdy (AL-TAHRIR, 2024)
The values of prophetic education contained in Surah al-Saffat: 99-111 hold significant relevance for Islamic education, particularly in addressing contemporary challenges in character and spiritual development. Understanding the educational approach of Prophet Ibrahim As. and its application to Prophet Ismail As., as narrated in these verses, provides critical insights into nurturing values aligned with Islamic teachings. This research aims to uncover the values of prophetic education conveyed in these verses and their relevance to modern Islamic education. Using a library research method, this study analyzes the prophetic narrative within Surah al-Saffat 99-111. The findings reveal core elements of Islamic education embedded in Prophet Ibrahim's teachings to his son, including obedience, patience, sincerity, and trust in Allah, which form the foundation of strong spiritual education. When these values are implemented in modern education, educators can foster students’ personalities grounded in Islamic spiritual principles, shaping a generation with noble character, faith in Allah, and a positive impact on their communities.